Clinical features of detrusor underactivity in elderly men without neurological disorders - Kiba, Keisuke; Akashi, Yasunori; Yamamoto, Yutaka; Hirayama, Akihide; Fujimoto, Kiyohide; Uemura, Hirotsugu (Lower urinary tract symptoms, 2022)
Objectives To investigate the clinical features of detrusor underactivity (DU) in elderly men without neurological disorders. Methods A total of 336 men aged ≥50 years without neurogenic disorders who underwent pressure flow studies and who had DU or bladder outlet obstruction (BOO) were reviewed retrospectively. According to the bladder contractility index (BCI) and the BOO index (BOOI), the subjects were classified into the following three groups: (a) pure DU group, BCI < 100 and BOOI < 40; (b) DU + BOO group, BCI < 100 and BOOI ≥ 40; and (c) pure BOO group, BCI ≥ 100 and BOOI ≥ 40. Subjective and objective parameters were compared among the three groups, and the predictors for pure DU were evaluated by multivariate analysis. Results Of the 336 patients, 205 who met the study criteria were included in the analysis: 63 (30.7%) with pure DU, 48 (23.4%) with DU + BOO, and 94 (45.9%) with pure BOO. The proportion of the pure DU group increased with increasing age. Prostate volume was the lowest in the pure DU group. Frequency, urgency on the International Prostate Symptom Score (IPSS), and the IPSS storage subscore were the lowest in the pure DU group. Multivariate analysis showed that age (odds ratio [OR] 1.114 [95% CI, 1.032‐1.203], P = .005), prostate volume (OR 0.968 [95% CI, 0.949‐0.987], P = .001), and urgency (OR 0.623 [95% CI, 0.431‐0.900], P = .012) were predictors of pure DU. Conclusion Older age, smaller prostate volume, and less urgency may be clinical features of pure DU.